A Sociolinguistic Study of Code Switching in the Lyrics of the Song "Tak Tun Tuang" by Upiak Isil - Layli Syafira Nasution; Sutikno (International Journal of Educational Research Excellence (IJERE), 2022)
The title of this research is: “A Sociolinguistic Study of Code Switching in the Song Lyrics of Tak Tun Pour by Upiak Isil”. The purpose of this study is to describe the types, forms, and reasons for code switching in the lyrics of the song Tak Tun Pour. The research method used is descriptive method. The data consists of quotations in the form of lines and stanzas of the song lyrics undergoing code switching. The analysis was carried out by clarifying the types, forms, and reasons for code switching based on the theory presented by Suwito. The results of data analysis show that the type of code switching that appears in the lyrics of the song Tak Tun Pour is internal code switching. The code switching that occurs is in the form of intersentential switching. The reason for code switching is adjusting to the language code controlled by the interlocutor, the inability to use the language code that is being used for a long time continuously and continuously, changes in the interlocutor, and the specific intentions of the speaker. The type of code switching that appears is inward code switching. Code switching that occurs is in the form of insertion of words, phrases, clauses and repetition of words.